REPRESENTATION OF FEMALES IN “MULAN” BY DISNEY - Raisa Amanda Putri; Clara Kalyana Ayusya; Irma Rasita Gloria Barus (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
One of the most memorable films from our childhood would be "Mulan" by Disney. When most of the Disney princesses show us the glamour, the elegance of being a princess, “Mulan” shows us something else, like a battlefield, army, war, and lots of other things that may sound new and fresh from a child's perspective. People watch Mulan on her journey to become China's saviour. Ignoring the line that separates a man from a woman she kept her head up and worked hard to become the perfect soldier for her land. Despite showing her capability in fight and strategies to help her comrades survive the battlefield, she still faces rejection and anger when people around her find out that she is a woman. But she still tries her best to save the country by protecting China's emperor when he faces life and death situations caused by the enemies. Her success caused a lot of people to acknowledge her power as a woman and praise her. This paper will study the female representation of “Mulan”. A qualitative method will be used to conduct this study to show educational values in “Mulan” by Disney.